2022
DOI: 10.3934/dcds.2021160
|View full text |Cite
|
Sign up to set email alerts
|

Eternal solutions for a reaction-diffusion equation with weighted reaction

Abstract: <p style='text-indent:20px;'>We prove existence and uniqueness of <i>eternal solutions</i> in self-similar form growing up in time with exponential rate for the weighted reaction-diffusion equation</p><p style='text-indent:20px;'><disp-formula> <label/> <tex-math id="FE1"> \begin{document}$ \partial_tu = \Delta u^m+|x|^{\sigma}u^p, $\end{document} </tex-math></disp-formula></p><p style='text-indent:20px;'>posed in <inline-formula>&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…the most interesting feature of this equation being the presence of an unbounded weight on the reaction term, which, as we shall see, has a very strong influence on the dynamics of it. In particular, the lower bound we impose σ > 2(1−p)/(m−1) is the optimal one leading to the phenomenon of finite time blow-up, which does not occur either for the non-weighted (homogeneous) equation with σ = 0 studied in [26,27,28] or even for the limiting case σ = 2(1−p)/(m−1), a case studied recently in [21] where it is shown that eternal solutions in self-similar exponential form exist.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…the most interesting feature of this equation being the presence of an unbounded weight on the reaction term, which, as we shall see, has a very strong influence on the dynamics of it. In particular, the lower bound we impose σ > 2(1−p)/(m−1) is the optimal one leading to the phenomenon of finite time blow-up, which does not occur either for the non-weighted (homogeneous) equation with σ = 0 studied in [26,27,28] or even for the limiting case σ = 2(1−p)/(m−1), a case studied recently in [21] where it is shown that eternal solutions in self-similar exponential form exist.…”
mentioning
confidence: 97%
“…(1.1) with σ = 0. We mention here also our recent work [21] in which the limits of the blow-up behavior are explored: it is proved there that for σ = 2(1 − p)/(m − 1), eternal solutions with exponentially fast grow-up in time exist and finite time blowup is not expected to occur for this limiting exponent. We thus deduce that the range of σ we consider is optimal with respect to finite time blow-up, and of course this illustrates the strong influence of the magnitude of σ on the dynamics of Eq.…”
mentioning
confidence: 99%
“…(1.1) is mapped onto the condition L = 0 for Eq. (1.5), where L is the constant defined in (1.9), and we already know from [31,20] that L = 0 is the necessary and sufficient condition in Eq. (1.5) to ensure the existence of eternal self-similar solutions in exponential form.…”
Section: Some More Transformationsmentioning
confidence: 99%
“…(1.9) Indeed, when L > 0, backward self-similar solutions as in (1.8b) have been constructed, while if L < 0, self-similar solutions are in forward form (1.8a). Eternal, exponential selfsimilar solutions have been constructed in the special case L = 0 in [31,32,20]. We end up this presentation by introducing here a constant related to L which will be very useful in the study of self-similar solutions to Eq.…”
Section: Introductionmentioning
confidence: 99%
“…(1.8) Indeed, when L > 0, backward self-similar solutions as in (1.7b) have been constructed, while if L < 0, self-similar solutions are in forward form (1.7a). Eternal, exponential self-similar solutions have been constructed in the special case L = 0 in [59][60][61]. We end up this presentation by introducing here a constant related to L, which will be very useful in the study of self-similar solutions to Equation (1.1):…”
Section: Self-similar Solutionsmentioning
confidence: 99%